2007
DOI: 10.1093/pcp/pcm101
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of a Foreign Aquaporin Disrupts the Natural Expression Patterns of Endogenous Aquaporin Genes and Alters Plant Responses to Different Stress Conditions

Abstract: Although the number of reports demonstrating the roles of individual aquaporins in plants under diverse physiological conditions is expanding, the importance of interactions between different aquaporin isoforms and their integrated functions under stress conditions remain unclear. Here, we expressed one cucumber aquaporin gene, designated CsPIP1;1, and one figleaf gourd aquaporin gene, designated CfPIP2;1, in Arabidopsis thaliana, and investigated the effect of its expression on the natural expression patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…Aquaporin abundance in root cortex cells may alter L o, especially during water shortage (Maurel et al, 2015), where aquaporins are thought to be regulated for the maintenance of the adequate water balance (Jang et al, 2007a,b). Among them, PIPs were proved to contribute to the adaptation of plants to drought episodes, also contributing to rehydration of the whole plant after water shortage (Maurel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Aquaporin abundance in root cortex cells may alter L o, especially during water shortage (Maurel et al, 2015), where aquaporins are thought to be regulated for the maintenance of the adequate water balance (Jang et al, 2007a,b). Among them, PIPs were proved to contribute to the adaptation of plants to drought episodes, also contributing to rehydration of the whole plant after water shortage (Maurel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Such effects may come from both the increase of GsTIP2;1 and the interactions of GsTIP2;1 with endogenous AQP or other genes. Though TIP is not a transcript factor, overexpression of TIP might become a signal and the expression of some endogenous genes might be influenced as described by Jang's study that the overexpression of some PIP genes from cucumber altered the expression of some AQP genes in Arabidopsis (Jang et al, 2007), and the tolerance may be altered by cooperation of GsTIP2;1 and some endogenous genes. In transgenic Arabidopsis plants, GsTIP2;1 is expressed constitutively ignoring growth phases and conditions, implying that an increase in exogenous GsTIP2;1 concentration may be deleterious for a plant under salt and dehydration stresses.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown that the over-expression of particular PIP isoforms promote tolerance to water stress [PIP1;4 and PIP2;5 - ( Jang et al 2007a)], other studies have shown that opposite responses can be produced. For example, the overexpression of cucumber PIP1;1 in Arabidopsis worsened plant performance under conditions of water stress, while the figleaf gourd PIP2;1 gene improved performance in Arabidopsis ( Jang et al 2007a, Jang et al 2007b. The overexpression of rice PIP1;1 or PIP2;2 genes in Arabidopsis induced greater tolerance to salt and drought (Guo et al 2006).…”
Section: Expression Of Aquaporins In Coffee Plants Under Drought Stressmentioning
confidence: 99%